60-GHz Millimeter-Wave Radio: Principle, Technology, and New Results. (18th December 2006) - Guo Guo, Nan Nan; Qiu Qiu, Robert C. Robert C.; Mo Mo, Shaomin S. Shaomin S.; Takahashi Takahashi, Kazuaki Kazuaki
Abstract : The worldwide opening of a massive amount of unlicensed spectra around 60 GHz has triggered great interest in developing affordable 60-GHz radios. This interest has been catalyzed by recent advance of 60-GHz front-end technologies. This paper briefly reports recent work in the 60-GHz radio. Aspects addressed in this paper include global regulatory and standardization, justification of using the 60-GHz bands, 60-GHz consumer electronics applications, radio system concept, 60-GHz propagation and antennas, and key issues in system design. Some new simulation results are also given. Potentials and problems are explained in detail.